If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -1x = 21 Solving 13 + -1x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -1x = 21 + -13 Combine like terms: 13 + -13 = 0 0 + -1x = 21 + -13 -1x = 21 + -13 Combine like terms: 21 + -13 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 6x+8=104 | | 12x^4-x^2-1=0 | | 5x+24=15x-56 | | 8z+13=6z+8 | | 5(4y-2)=10y | | 3r-3=3r+5 | | 6(2-9x)=2x-7 | | 9x^4-72x^2+64=0 | | 5abc=y | | .40x+.05(200)=.20(54) | | 10x=9x-30 | | 8798x-9088=78 | | -4(3p+2)-28=3(2p+6) | | -5(-3-2z)=11z | | 12m-9=q | | -2(x+5)-5=-15 | | 3p+2(0.5p)=120 | | 6(7x-1)+5=24+3x | | 2c-7=15 | | y+2=-1+6 | | 8t+3=45 | | 77-5x=31x+21 | | -68=17y | | 6x^2+48x+96= | | 12-10x=84-31x | | 4p+7p= | | 5x^2+24x-5=0 | | 22x+8-26x=4-8 | | 4(a)+1-a=1919 | | 6(7x-1)+5=24+x | | k-5=-42 | | -14-3x=14-7x |